Research on the in vitro Antibacterial Activity and in vivo Anti-inflammatory and Analgesic Functions of Paederia scandens Extracted by Ethanol - Ningyu YANG; Jiali JIANG; Shuying LIANG; Lin ZENG; Hongying LIN; Jinjun CHEN; Danju KANG (Guangdong nongye kexue, 2022)
【Objective】The antibacterial effect in vitro and the anti-inflammatory and analgesic effects in vivo of the effective active components of Paederia scanden were explored in order to provide theoretical support for the full utilization of P. scanden resources.【Method】The P. scanden was extracted with 40% ethanol solution, and the chemical components of the extract were preliminarily analyzed. The antimicrobial activities of the extract to Escherichia coli, Salmonella, Staphylococcus aureus and Bacillus cereus were detected by drug sensitivity test and double gradient dilution method to determine the minimum inhibitory concentration (MIC). The anti-inflammatory effect of P. scanden was explored by relieving xylene-induced ear swelling in mice and carrageenan-induced mice foot swelling. And the analgesic effect of acetic acid-induced writhing pain in mice was studied.【Result】The ethanol extract of P. scanden contained many effective chemical components such as flavonoids and terpene lactones, which could inhibit the growth of B. cereus, with the inhibitory zone diameter of 8.55 mm and MIC of 500 mg/mL, but the antibacterial effect on E. coli, Salmonella and S. aureus was not obvious. Compared with the control group, the inhibitory rates of medium and high doses of P. scanden extract on mice ear swelling induced by xylene were 30.93% and 55.00%, and the inhibition rates of mice foot swelling induced by carrageenan were 49.74% and 58.26%, respectively, showing extremely significant anti-inflammatory effects, and they could effectively alleviate peripheral pain caused by glacial acetic acid in mice, delaying the time of the first writhing reaction in mice and reducing the frequency of writhing reaction within 15 minutes.【Conclusion】The ethanol extract of P. scanden contains rich medicinal activity. Although the antibacterial effect in vitro is weak, the anti-inflammatory and analgesic effects on tested mice are remarkable. Therefore, it can be used as one of the candidate Chinese herbal resources for animal feed additives.